EVIDENCE- BASED ACTION PLAN OF REHAB CENTERS FOR PATIENTS WITH LOW BACK PAIN - Ulysses M. Cutamora, (Malaysian Journal of Medical Research (MJMR), 2018)
<span style="color: #000000; font-family: 'times new roman', times, serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #f4f2e9; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Back pain is common and many people experience long term problems. The goals of physical therapy are to decrease back pain, increase function and provide health education. Low back pain (LBP) is pain, muscle tension, or stiffness localized below the costal margin and above the inferior gluteal folds, with or without sciatica, and is defined as chronic when it persists for 12 weeks or more. The study objective is to enhance the compliance of Patients to Rehabilitation Regimen to achieve better prognosis and treatment outcomes. The respondents of the study were low back pain patients from three (3) different rehabilitation centers, Rehabilitation Medicine of Cebu Velez General Hospital, Rehab Solutions Incorporated in Perpetual Succor Hospital and Rehab Medics of Chong Hua Hospital. To answer the mean characteristics of the respondents, descriptive statistical procedures were utilized. To determine the differentiating factors, discriminant analysis was used while logistic regression was utilized to determine the predictors of therapy outcomes. This study utilized a quantitative descriptive research design which enabled the researcher to determine if there exists a relationship between the therapy outcomes as the dependent variable to the demographic, employment and clinical variables identified in the study. It can therefore be concluded that of the twelve (12) variables explored, only four (4) clinical variables are significant predictors of low back pain treatment outcomes. These are (a) compliance to treatment regimen, (b) Co-morbidity, (c) Surgical history and (d) Type of low back pain. The rehabilitation centers would take into consideration the results of the study and that they will find a better way encourage compliance of patients to rehabilitation treatment utilizing the proposed evidence-based action plan. With this development, the problem with regard to compliance and result of rehabilitation treatment will be addressed and will greatly contribute to overall wellness and successful outcome of low back pain treatment. It is therefore imperative that physical therapists should focus on these clinical variables in treating for patients with LBP and recommended that rehabilitation centers should follow the evidence-based action plan.